THE USE OF LISTENING LOGS THROUGH WHATSAPP IN IMPROVING LISTENING COMPREHENSION OF EFL STUDENTS - Iwan Fauzi; Putri Angkasawati (Universitas Bengkulu, 2019)
The objective of this study is to find out the effect of using listening logs through WhatsApp on listening comprehension of EFL students in the Department of English Education of Palangka Raya University. The listening comprehension of students is categorized low which hampers their proficiency in English. Then an experiment is done to improve students’ comprehension in listening skill by using listening logs through WhatsApp application on smartphones. The experiment treated in this study was to make a learning group of WhatsApp by inviting the students joining the group. The experiment was held for three weeks which practiced four aspects of listening comprehension: (1) identifying main ideas or main gists, (2) identifying supporting details, (3) identifying moods of message, and (4) developing new vocabularies. There were 40 students (24 females and 16 males) fulfilling the sample of the study taken from the second year EFL students of English study program at Palangka Raya University. The method used in this study was pre-experimental design by choosing the type of one group pretest-posttest design. The pretest and posttest evaluation results were analyzed using non-parametric test of Wilcoxon Signed-ranks by two-related samples statistical analysis to find out the significance of the experiment given. The study concludes that the practice of listening through listening logs in WhatsApp gives significant improvement in listening comprehension to EFL learners.Keywords: listening logs, WhatsApp, EFL students